2020
DOI: 10.3389/fphys.2019.01561
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor (AhR) in the Aging Process: Another Puzzling Role for This Highly Conserved Transcription Factor

Abstract: Aging is the most important risk factor for the development of major life-threatening diseases such as cardiovascular disorders, cancer, and neurodegenerative disorders. The aging process is characterized by the accumulation of damage to intracellular macromolecules and it is concurrently shaped by genetic, environmental and nutritional factors. These factors influence the functionality of mitochondria, which play a central role in the aging process. Mitochondrial dysfunction is one of the hallmarks of aging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 106 publications
1
42
0
1
Order By: Relevance
“…Since its discovery, the variety of pathophysiological processes regulated by the AhR has rapidly grown and range from cell death, to immune response and neuronal development [ 6 ]. Contradictory studies also indicated a role for AhR in the aging process (reviewed in [ 7 ]) and more recently, pro-aging functions of AhR [ 8 , 9 ] have been described in an evolutionarily conserved manner from C. elegans to mammals. In mammals, in basal conditions, AhR is bound to heat shock protein 90 (HSP90), AhR interacting protein (AIP), and p23, which retain it in the cytoplasm, in a ligand-affine state.…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery, the variety of pathophysiological processes regulated by the AhR has rapidly grown and range from cell death, to immune response and neuronal development [ 6 ]. Contradictory studies also indicated a role for AhR in the aging process (reviewed in [ 7 ]) and more recently, pro-aging functions of AhR [ 8 , 9 ] have been described in an evolutionarily conserved manner from C. elegans to mammals. In mammals, in basal conditions, AhR is bound to heat shock protein 90 (HSP90), AhR interacting protein (AIP), and p23, which retain it in the cytoplasm, in a ligand-affine state.…”
Section: Introductionmentioning
confidence: 99%
“…curcumin, UVB and BaP). The differential effects on lifespan and gene expression we observed upon ahr-1 genetic-or RNAi-mediated suppression interestingly reveal the importance of fine-tuning its activity in a dose and/or tissue-dependent manner, which very nicely recapitulate the variety of phenotypic features described in mammals upon dosage effects or tissue-specific depletion (Brinkmann et al, 2020). Moreover, to our surprise, we found that besides increased resistance to heat-shock, lack of ahr-1 did not confer resistance to any other investigated insult, such as metabolic stress or radiation, and in fact sensitize animals to UVB.…”
Section: Discussionmentioning
confidence: 68%
“…Since its discovery, the variety of pathophysiological processes regulated by the AhR has grown and range from cell death, to immune response and neuronal development (Esser, Lawrence et al, 2018). Contradictory studies also indicated a role for AhR in the aging process (reviewed in (Brinkmann, Ale-Agha et al, 2020)) and more recently, pro-aging functions of AhR (Eckers, Jakob et al, 2016, Williams, Mouchiroud et al, 2014 have been described in an evolutionarily conserved manner from C. elegans to mammals. In mammals, in basal conditions, AhR is bound by HSP90, AIP, and p23, which retain it in the cytoplasm, in a ligand-affine state.…”
Section: Introductionmentioning
confidence: 99%
“…These authors also found the AhR to be increased in the serum of Alzheimer’s disease patients. Many studies have shown the AhR to be relevant to the ageing process, promoting an ageing phenotype across different species, which the authors propose to be mediated via effects on mitochondrial function [ 173 ]. The levels of AhR over age in different organs and tissues, and especially in immune cells, will be important to determine, including in correlation with SARS-CoV-2 infection severity.…”
Section: Future Researchmentioning
confidence: 99%